The Gardening Handbook - McHoy, Peter (Enderby Abbeydale Press, 1998)
Gardening is by far the most popular and widespread leisure activity in the world. This book is not only the ideal practical introduction for new enthusiasts but also a comprehensive reference book for the more experienced gardener. In gardening, satisfaction comes from success, and The Gardening Handbook shows you how to get the best results every time.--From publisher description.
Include Color Illustrations and Index
Keywords: Gardening -- Pruning